HUBUNGAN JUMLAH KUNJUNGAN ANTENATAL DENGAN ANGKA KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS MARGADADI KABUPATEN INDRAMAYU TAHUN 2022 - Najma Zahirah, (2023)
Stunting is a condition where a child's height does not match their age caused by persistent nutritional disorders. The incidence of stunting in the Indramayu area is quite high, namely 29.19% in 2019 which exceeds the WHO target of 20%. Antenatal visits indirectly induce stunting since stunting factors can be seen prenatally. Antenatal visits are a series of comprehensive examinations for pregnant women. The Indonesian Ministry of Health's 2021 recommendations divide antenatal visits into the first (K1), fourth (K4), and sixth (K6) visits. The purpose of this research is to discover the relationship quantity of antenatal visits and the incidence of stunting in toddlers in the Margadadi Puskesmas Working Area, Indramayu Regency. A case-control design was used in the research. The population were moms of toddlers, and the sample size was 60 respondents taken by consecutive sampling with 30 respondents each as a case and control group. This study's dependent variable was toddlers with stunting conditions, whereas K1, K4, and K6 were the independent variables. Both univariate and bivariate analyses were used in this research's analysis. The findings of this research indicate that there is a relationship between K6 and stunting incidence (p = 0.038; OR= 0.196; 95% CI= 0.038 - 1.020). It was found that only K6 was related to stunting. Therefore, it can be concluded that the application of K6 will significantly reduce the risk of growth disorders in toddlers, especially stunting.